Rectified activity-dependent population plasticity implicates cortical adaptation for memory and cognitive functions - Hong Xie; Kaiyuan Liu; Dong Li; Chang-Shui Zhang; Claus C. Hilgetag; Ji-Song Guan (Communications Biology)
Abstract Cortical network undergoes rewiring everyday due to learning and memory events. To investigate the trends of population adaptation in neocortex overtime, we record cellular activity of large-scale cortical populations in response to neutral environments and conditioned contexts and identify a general intrinsic cortical adaptation mechanism, naming rectified activity-dependent population plasticity (RAPP). Comparing each adjacent day, the previously activated neurons reduce activity, but remain with residual potentiation, and increase population variability in proportion to their activity during previous recall trials. RAPP predicts both the decay of context-induced activity patterns and the emergence of sparse memory traces. Simulation analysis reveal that the local inhibitory connections might account for the residual potentiation in RAPP. Intriguingly, introducing the RAPP phenomenon in the artificial neural network show promising improvement in small sample size pattern recognition tasks. Thus, RAPP represents a phenomenon of cortical adaptation, contributing to the emergence of long-lasting memory and high cognitive functions.